Nutritional profile of pregnant women assisted in the first prenatal nutritional consultation in a philanthropic institution from São Paulo - Moreira Nochieri, Ana Carolina; Figueiredo de Assumpção, Magali; Lama Belmonte, Flávia Aparecida; Azevedo Leung, Maria do Carmo (O Mundo da Saúde, 2008)
Individualized nutritional evaluation in the beginning of the prenatal period is important to establish pregnant women nutritional necessities in this period and must be carried out continuously along pregnancy. The present study had as its aim to analyze the nutritional profile by surveying the registers contained in a database of 219 pregnant women attended in first prenatal consultation in the Outpatient Department of Amparo Maternal, a philanthropic institution. The studied pregnant women had an average 24.3 years, most single, with incomplete secondary education and pertaining to E class. Regarding the first prenatal nutritional consultation, 73.9% began in the 3rd gestation term, and most were primigravid. As for nutritional condition, it was noticed that from pre- gestational to gestational state there was a fall in the classification of low weight and eutrophy, and an increase of overweight. Food taken was on average below the recommended energetic values (2029 kcal and 2146 kcal, for adolescent and adult pregnant women, respectively) and as for the distribution of macronutrients carbohydrates and lipids were adequate and proteins above WHO recommendations. Regarding micronutrients, it was noticed that calcium and vitamin A were insufficient, and vitamin C above recommendations, an indication of the importance of assistance by a professional nutritionist in prenatal consultations for promoting educative actions directed to correct eating habits.